States and needs of information and digital knowledge access training in government services in Satun province, Thailand - Saengtong, Thanidaphat; Kaewsuwan, Nawapon; Theppaya, Thapanee (International Journal of Innovative Research and Scientific Studies, 2024)
This research aimed to study the state and needs of information and digital knowledge access training. The research was conducted using a mixed method with in-depth interviews. Digital literacy training is an important issue for reducing inequality in access to information and digital knowledge, which is important to living, occupation, and basic rights. A group discussion of 30 people and a questionnaire with a group of 405 people were used in urban-style communities and rural-style communities. They were in the community area, aged from 20 to 59 years old, and recruited with a specific method according to the rural-urban continuum model by Dewey. Data were analyzed by content-based synthesis according to the classification approach and statistical methods. It was found that (1) current states of accessing information and digital knowledge are problematic in terms of access to signals, networks, and the management of community leaders. Overall, the state of information and digital knowledge access was at a moderate level. (2) For training needs, it was found that there was unstable and unequal access and disparity in all areas. What is needed is to support the reduction of inequality in access to information and knowledge by involving all agencies in creating a training curriculum. Overall, the attitudes and demands for accessibility training were at a moderate level. The result can be used as a guideline regarding cooperation among local government agencies to participate in analyzing conditions, problems, and needs in accessing information and digital knowledge according to the basic rights of the people.